Effect of surface chemistry on bio-conjugation and bio-recognition abilities of 2D germanene materials - Ang, Wei Li (2022)
The interest of the scientific community for 2D graphene analogues has been recently focused on 2D-Xene materials from Group 14. Among them, germanene and its derivatives have shown great potential because of their large bandgap and easily tuneable electronic and optical properties. With the latter having been already explored, the use of chemically modified germanenes for optical bio-recognition is yet to be investigated. Herein, we have synthesized two germanene materials with different surface ligands namely hydrogenated germanene (Ge-H) and methylated germanene (Ge-Me) and used them as an optical platform for the label-free biorecognition of Ochratoxin A (OTA), a highly carcinogenic food contaminant. It was discovered that firstly the surface ligands on chemically modified germanenes have strong influence on the intrinsic fluorescence of the material; secondly they also highly affect both the bio-conjugation ability and the bio-recognition efficiency of the material towards the detection of the analyte. An improved calibration sensitivity, together with superior reproducibility and linearity of response, was obtained with a methylated germanene (Ge-Me) material, indicating also the better suitability of the latter for real sample analysis. Such research is highly beneficial for the development and optimization of 2D material based optical platforms for fast and cost-effective bioassays.